2006
DOI: 10.1002/ange.200504495
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Gold‐Catalyzed Hydroamination of 1,3‐Dienes

Abstract: Ein Hauch von Gold: 1,3‐Diene werden in Gegenwart von Ph3PAuOTf als Katalysator durch Carbamate und Sulfonamide unter milden Bedingungen hydroaminiert (siehe Schema). Die Cbz(Carbobenzyloxy)‐Gruppe lässt sich einfach vom Produkt abspalten, sodass die Reaktion einen effizienten Zugang zu einer Vielzahl allylischer Amine bietet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(14 citation statements)
references
References 41 publications
0
13
0
1
Order By: Relevance
“…It should be mentioned that after deprotection of the nitrogen, substrate 11 could be converted to product 6k under the standard reaction conditions of the gold catalysis (Scheme 6). Nevertheless, the reaction rates for the hydroamination of the 1,3-diene [26] 11 turned out to be much slower than for the cycloisomerization of the corresponding allene 5k (incomplete conversion after 72 h instead of complete conversion after 1 h for the allene). This indicates that the stepwise sequence is only a minor alternative pathway that leads to the same final product.…”
Section: Resultsmentioning
confidence: 96%
“…It should be mentioned that after deprotection of the nitrogen, substrate 11 could be converted to product 6k under the standard reaction conditions of the gold catalysis (Scheme 6). Nevertheless, the reaction rates for the hydroamination of the 1,3-diene [26] 11 turned out to be much slower than for the cycloisomerization of the corresponding allene 5k (incomplete conversion after 72 h instead of complete conversion after 1 h for the allene). This indicates that the stepwise sequence is only a minor alternative pathway that leads to the same final product.…”
Section: Resultsmentioning
confidence: 96%
“…[1] Recently, in-depth kinetic and mechanistic studies on the gold(I)catalyzed nucleophilic addition to a carbonÀcarbon unsaturated bond have been published, with the aim to understand the ligand effect [2] and to isolate and characterize the intermediates involved in the catalytic cycle. [3, 4] However, also the anion can influence the catalytic activity, [5] the regioselectivity, [6] and even the stereoselectivity [7] of the process. Moreover, it has been observed that the anion can influence the structure of the catalyst [8] and of the intermediates in the catalytic cycle.…”
mentioning
confidence: 99%
“…In practice, the vast majority of reported diene hydroamination reactions are selective for the formation of allylic amines. [3] In particular, known hydroamination reactions catalyzed by nickel or palladium give exclusively allylic amines, owing to the intermediacy of an h 3 -allyl complex. [4] Similarly, Brønsted acid catalyzed hydroamination reactions also generate allylic amines, as predicted by the stability of the intermediate allyl cation.…”
mentioning
confidence: 99%